Model Strategi Komunikasi Interpersonal Empatik dalam Pembelajaran Inklusif Anak Berkebutuhan Khusus : Studi Kasus di SLB Negeri Gianyar - putu atik (Dharma Duta, 2026)
This study aims to develop a model of empathetic interpersonal communication strategies in inclusive education for children with special needs at the Gianyar State Special Education School. The study was motivated by the complexity of communication interactions between teachers and students who exhibit diverse cognitive, emotional, social, and sensory characteristics, such that an instructional approach to communication has not been able to holistically meet their learning needs. The study employed a qualitative approach using the case study method to explore communication practices in a natural context. Data collection was conducted through participatory observation, in-depth interviews with teachers as the primary informants, and documentation. Data analysis utilized an interactive model involving the stages of data reduction, data presentation, and the derivation and verification of conclusions. The research findings indicate that empathetic interpersonal communication strategies are built through three main, mutually integrated dimensions: the affective, adaptive, and reflective dimensions. The affective dimension emphasizes teachers’ ability to build emotional closeness and empathy toward students. The adaptive dimension reflects teachers’ flexibility in adjusting their communication styles, media, and delivery methods to meet students’ needs. The reflective dimension emphasizes continuous evaluation of communication practices as an effort to enhance pedagogical professionalism. This study also found that the integration of local wisdom values, particularly the concept of Tat Tvam Asi, strengthens communication practices that are humanistic, inclusive, and oriented toward respect for diversity. Based on these findings, the study developed a conceptual model of empathetic interpersonal communication strategies that is integrative, contextual, and practical. This model contributes to the development of research on inclusive educational communication and can serve as a guideline for teachers and stakeholders in designing more effective, responsive, and equitable learning communication.